Απόφαση του Δημοτικού Συμβουλίου σχετικά με την τροποποίηση του προϋπολογισμού χρήσεως 1947-48ως προς τα έσοδα και τα έξοδα
Απόφαση του Δημοτικού Συμβουλίου σχετικά με την τροποποίηση του προϋπολογισμού χρήσεως 1947-48ως προς τα έσοδα και τα έξοδα